Ethics and Moral Education - Eegunlusi, Tayo Raymond Ezekiel (African Journal of Stability and Development (AJSD), 2024)
This paper discusses the idea of ethics is in relation to the possibility and attainment of moral education. It is informed by the belief that adequate attention to ethical thinking is essential in attaining moral satisfaction and developing the society. The study emphasises the importance of critical moral self- examination and good moral education. It identifies and examines three essential types of ethics in relation to moral self-examination and moral education. It equally examines who a moral agent is and how well the pursuit of self-interest should be understood. Through conceptual clarification, analysis and reflection on certain theoretical views in philosophy, such as the views of Buddha, Socrates, Aristotle and the Yoruba concept of ìwòntúnwònsì, it argues for the expediency of moderation in achieving moral education. It also shows that deficiencies in human conduct limit any human that is not morally educated from leading a morally satisfying life.